Podcasting in the teaching of listening skills to general superior basic school students. - Mosquera Arguello, Luz Magali (2024)
The use of podcasts is of paramount importance in strengthening listening skills in English language learning. However, during the teaching-learning process, teachers at the Pedro Vicente Maldonado School neglect the use of technological media such as podcasts to teach listening skills, leading to weaknesses in students' ability to discriminate phonemes, syllables, intonation, accent, and non-verbal language. This study aimed to investigate the impact of podcasts on listening skills in student learning using both quantitative and qualitative research methods. The research was conducted using the descriptive research design, which helped to describe how the object of study is found. The methods used in this study were theoretical and empirical, which allowed us to comprehensively address the object of study. A questionnaire was applied to students in the tenth year. The research revealed that students of English of tenth year might improve their listening skills by using podcasting. Therefore, it is essential to provide high schools with trained teachers, technological tools, and financial resources to enhance the teaching of listening skills, which will ultimately improve the learning of English.